Fairness electronic payment protocol. (2nd March 2012) - Fan, Kai; Wang, Yue; Li, Hui
Abuse-freeness is one of the most interesting new problems in the electronic payment security today. It is an effective supplementary for the fairness. It is confusing to researchers how to get real abuse-freeness in electronic payment. An abuse-freeness electronic payment protocol for real goods is proposed in this paper. The protocol has the abuse-freeness by introducing a trusted third party and using the concurrent signature and it has prevented both sides in payment to originate and terminate protocol maliciously. At the same time fairness and security are also achieved in the proposed protocol.